1955
DOI: 10.1113/expphysiol.1955.sp001130
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Interaction of Chyle and Plasma in the Rat

Abstract: WHEN a rat is absorbing olive oil from its intestine there is a marked increase in the ability of its plasma to clear chyle added to it in vitro [Jeffries, 1954 Further studies made on these clearing systems, demonstrable in vitro after olive oil feeding and after the injection of small quantities of heparin, are reported in this paper. METHODSWistar strain albino rats, fed a laboratory stock diet containing 2 per cent fat, were used. All animals were starved for 16 hours before olive oil was fed or heparin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1955
1955
1994
1994

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Earlier in vitro studies showed that lipoprotein lipase becomes strongly absorbed on to chylomicrons (D.5. Robinson et al, 1955).…”
Section: Transport Of Substrates Into Mammary Cellsmentioning
confidence: 95%
“…Earlier in vitro studies showed that lipoprotein lipase becomes strongly absorbed on to chylomicrons (D.5. Robinson et al, 1955).…”
Section: Transport Of Substrates Into Mammary Cellsmentioning
confidence: 95%
“…A lipolytic system similar to that induced by injection of heparin has been demonstrated in rat plasma during fat absorption [Jeffries, 1954;Robinson, Jeffries and French, 1954;Robinson, Jeffries and Poole, 1955]. The ability of chyle to maintain the lipolytic activity of heparinized plasma, after heparin has been removed by a resin column, suggests that the presence of lipid particles in plasma after a fat meal may result in a stabilization of the plasma lipolytic activity and so allow its demonstration in vitro.…”
Section: Discussionmentioning
confidence: 94%
“…The rats were bled after 14 minutes and the clearing activities of their plasmas determined in the usual way. From these activities an approximate estimate of the amount of heparin injected could be made from a knowledge of the clearing activity to be expected after the injection of known amounts of heparin [Robinson, Jeffries and Poole, 1955].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remesow [1929] observed that tributyrinase activity was reduced in rabbit plasma following cholesterol feeding and attributed this to a reversible adsorption of lipase by plasma cholesterol. Clearing factor is also adsorbed at the surface of lipoid particles [Anfinsen and Quigley, 1953;Robinson, Jeffries and Poole, 1955], and it seems probable therefore that lipoid components of plasma which are inert in the clearing reaction may be capable of adsorbing part of the available clearing factor. This may account also for the changes in electrophoretic mobility of the 3 lipoproteins which have been observed following heparin injection in rabbits fed cholesterol [Comfort, 1955].…”
Section: Discussionmentioning
confidence: 99%